2016
DOI: 10.22146/ijg.9254
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Dynamics and Imperatives for Food Security in Nigeria

Abstract: Decadal variability in African rainfall is projected from General Circulation Models (GCMs) to continue under elevated greenhouse gas scenarios. Effects on rain intensity, spatio-temporal variability of growing seasons, flooding, drought, and land-use change impose feedbacks at regional-local scales. Yet, empirical knowledge of associated impacts on crop yield is limited; thus, we examined the imperatives for food security in Nigeria. Bivariate correlation and multiple regression suggests impending drought in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Our results revealed that climate change had been extensively experienced within the sampled African countries, with floods and extreme temperatures being experienced in West Africa, mostly in Ghana and Nigeria. The revelation is confirmed by several studies in the reviewed literature of this study [ 50 , 59 , 64 , 65 ]. Drought and extreme temperatures have also been experienced in the Eastern African countries, specifically in Ethiopia and Kenya; meanwhile, the Southern African countries (South Africa and Namibia) also experienced much drought and extreme temperatures.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results revealed that climate change had been extensively experienced within the sampled African countries, with floods and extreme temperatures being experienced in West Africa, mostly in Ghana and Nigeria. The revelation is confirmed by several studies in the reviewed literature of this study [ 50 , 59 , 64 , 65 ]. Drought and extreme temperatures have also been experienced in the Eastern African countries, specifically in Ethiopia and Kenya; meanwhile, the Southern African countries (South Africa and Namibia) also experienced much drought and extreme temperatures.…”
Section: Discussionsupporting
confidence: 85%
“…The severity of atmospheric warming causes low crop production, which has, in turn, increased food insecurity and shifted the population’s attention to imported food, which affects the livelihood of the vulnerable in Nigeria, South Africa, and Ghana [ 50 , 51 , 52 , 53 ], as well as causing malnutrition among children in Ethiopia [ 54 ]. A study in Ethiopia concluded that about 2.7 million people required emergency food assistance in 2014, while 238,761 children had treatment for severe and acute malnutrition [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…50 Nigeria spends over a trillion naira annually on food imports: N635 billion on wheat; N356 billion on rice; N217 billion on sugar; and N97 billion on fish. 51 This creates an additional financial burden for the country while increasing vulnerability to price volatility in the global market. Food importation also has safety implications, especially when they come from countries with low safety standards such as China.…”
Section: Food Importation Affordability and Safetymentioning
confidence: 99%